AUTOIMMUNE NATURE OF PSORIASIS: METAPHYLAXIS AND THE ROLE OF DERMATOLOGICAL MEANS IN MAINTAINING REMISSION - Bondarenko , Yaroslav; Bilovol , Alla (Collection of scientific papers «ΛΌГOΣ», 2025)
Relevance. Psoriasis is a chronic autoimmune disease characterized by excessive epidermal cell growth, inflammation, and scaling of the skin surface, which can manifest as scaly patches or plaques. Psoriasis is a chronic autoimmune disease affecting the skin with a systemic nature that significantly complicates its treatment and management. This condition is accompanied by excessive keratinocyte proliferation, inflammation, and skin regeneration disorders, leading to erythematous-squamous rashes. The most obvious manifestations of psoriasis are red, scaly patches and plaques that cause not only physical discomfort but also social difficulties due to social stigmatization and emotional distress.